Aquaculture in Maritime Spatial Planning Frameworks and Its Contribution to Global Food Security - Øivind Strand; Hui Liu; Joao G. Ferreira; Ramon Filgueira; Ellen Sofie Grefsrud; Pia Kupka Hansen; Qianwen Sun; Jenny Weitzman (Reviews in Aquaculture, 2026)
Increase in aquaculture toward realizing the potential of the ocean as a key food provider requires comprehensive and proactive management approaches to mitigate impacts on coastal areas and to secure space for sustainable aquaculture development in both inshore and offshore areas. Maritime Spatial Planning (MSP) and Marine Functional Zoning (MFZ) are policy instruments employed in the management and regulation of multiple human activities to balance social, economic, and environmental objectives. This work reviews the processes and stages of aquaculture integration into these marine spatial planning frameworks (MSP and MFZ) in major producers, China, the EU, Norway, and Canada. Implementation of aquaculture in the spatial planning frameworks varies widely, partly because the nations reviewed are at different stages of aquaculture development, and partly due to the heterogeneity of institutions, traditions, social acceptance, marine space, and governance. The common challenge of aquaculture impacts and interactions with the environment contribute to the complexity of regulating space for mariculture development. The apparent weak and in some cases receding position of aquaculture in the maritime spatial planning frameworks reviewed here warrants considerable concern with respect to expectations of marine aquaculture as a route for ensuring future seafood provision. There is a need to strengthen the position of aquaculture in marine spatial planning frameworks, particularly when considering its expansion in areas with potential for development. It is recommended that the global scientific, management, and regulatory communities work together with local actors to develop and provide accessible tools that will address sustainability challenges ahead.

Global stakeholder vision for ecosystem‐based marine aquaculture expansion from coastal to offshore areas - Ibon Galparsoro; Arantza Murillas; Kemal Pinarbasi; Ana M.M. Sequeira; Vanessa Stelzenmüller; Ángel Borja; Anne Marie O´Hagan; Adele Boyd; Suzanne Bricker; Joxe Mikel Garmendia; Antje Gimpel; Aline Gangnery; et al. (Reviews in Aquaculture, 2020)
Marine aquaculture is the most promising industry for ensuring future provision of seafood. Yet, the worldwide growth and expansion of this industry have been slower than expected, calling for the identification of environmentally suitable sites while accounting for all factors that could constrain or benefit its establishment. Here, we determine the main obstacles and risks hindering the growth and expansion of marine aquaculture, as well as the needs and recommendations to overcome such constraints. Our analysis is based on results obtained from a consultation process held in 16 study sites located around the world with the participation of 614 stakeholders representing the research community, aquaculture industry, government, conservation groups, and education and fishermen associations. A high level of commonality exists in the main issues hindering aquaculture growth and expansion in coastal, off‐the‐coast and offshore aquaculture with most being attributed to interactions with other maritime activities, including conflicts with other users and administrative procedures, including licensing. Critical needs for improved management and expansion of the aquaculture industry are related to planning and management of developments and technological advances, with economic and market needs featuring to a lesser extent. Key procedures recommended to assist further aquaculture growth are the standardisation and simplification of regulatory frameworks, improvement of governance, and the adoption of participatory processes to facilitate meaningful and productive stakeholder engagement. We strongly recommend stakeholder participation to enhance insights on the full environmental and human dimensions of marine management and for implementation of ecosystem‐based marine spatial planning.

Attraction and repulsion of mobile wild organisms to finfish and shellfish aquaculture: a review - Myriam D. Callier; Carrie J. Byron; David A. Bengtson; Peter J. Cranford; Stephen F. Cross; Ulfert Focken; Henrice M. Jansen; Pauline Kamermans; Anders Kiessling; Thomas Landry; Francis O'Beirn; Erik Petersson; et al. (Reviews in Aquaculture, 2018)
Knowledge of aquaculture–environment interactions is essential for the development of a sustainable aquaculture industry and efficient marine spatial planning. The effects of fish and shellfish farming on sessile wild populations, particularly infauna, have been studied intensively. Mobile fauna, including crustaceans, fish, birds and marine mammals, also interact with aquaculture operations, but the interactions are more complex and these animals may be attracted to (attraction) or show an aversion to (repulsion) farm operations with various degrees of effects. This review outlines the main mechanisms and effects of attraction and repulsion of wild animals to/from marine finfish cage and bivalve aquaculture, with a focus on effects on fisheries‐related species. Effects considered in this review include those related to the provision of physical structure (farm infrastructure acting as fish aggregating devices ( FAD s) or artificial reefs ( AR s), the provision of food (e.g. farmed animals, waste feed and faeces, fouling organisms associated with farm structures) and some farm activities (e.g. boating, cleaning). The reviews show that the distribution of mobile organisms associated with farming structures varies over various spatial (vertical and horizontal) and temporal scales (season, feeding time, day/night period). Attraction/repulsion mechanisms have a variety of direct and indirect effects on wild organisms at the level of individuals and populations and may have implication for the management of fisheries species and the ecosystem in the context of marine spatial planning. This review revealed considerable uncertainties regarding the long‐term and ecosystem‐wide consequences of these interactions. The use of modelling may help better understand consequences, but long‐term studies are necessary to better elucidate effects.